Articular Cartilage Damage in the Patellofemoral Compartment at ACL Reconstruction Predicts Poor Postoperative Subjective Outcomes in Patients Age 40 and Older - Miyamoto, Ayato; Nakamae, Atsuo; Tsukisaka, Kazuhiro; Deie, Masataka; Fujimoto, Eisaku; Soda, Yoshinori; Shimizu, Ryo; Adachi, Nobuo (The Journal of Knee Surgery, 2024)
The purpose of this study was to investigate factors that influence clinical outcomes after anterior cruciate ligament (ACL) reconstruction in patients aged ≥40 years. We studied 264 patients aged ≥40 and 154 patients aged ≤20 years who underwent ACL reconstruction at several surgical centers. A logistic regression analysis was conducted to identify factors that influenced the Knee Injury and Osteoarthritis Outcome Score (KOOS) at 1 year post-ACL reconstruction. In the older patient group, cartilage damage in the patellofemoral compartment at surgery was a significant risk factor for poor postoperative KOOS subscores (pain, activities of daily living [ADL], sports, and quality of life [QOL]). Articular cartilage damage in the lateral compartment also significantly influenced one of the postoperative KOOS subscores (symptoms). In the younger patient group, articular cartilage damage in any compartments did not influence the postoperative KOOS subscores; only two preoperative KOOS subscores (symptoms and QOL) significantly influenced their postoperative KOOS subscores. We concluded that the articular cartilage damage in the patellofemoral compartment at ACL reconstruction predicts poor KOOS subscores at the 1-year follow-up in patients aged ≥40 years.Study Design Cohort study (Prevalence); Level of evidence, 2.
Keywords: anterior cruciate ligament reconstruction; patients aged ≥40 year; articular cartilage damage; patellofemoral compartment